O avesso de uma trajetória docente - Silva, Rosa Tânia da (2016)
The following dissertation THE REVERSED PATH OF THE DOCENTS concerns about developing ways of proper understanding the reasons that generated and leaded to the one main research THE POETRY IN THE TEACHING OF VISUAL ARTS: IMAGETICS ON THE SCHOLASTIC PROEJA/IFPB that has been rejected by the Program from Postgraduate Level Studies from IFPB/IFPE at the date 30 march 2016. The final examining board pointed out the following reasons: a) high level of the present docents; b) insufficient time for the pratical camp field researched fields; c) little aesthetic development of educated, were the main motivations that resulted on the not nonapprovement. To share new lights and clarify the reasons why on this decisions turned into a new object of a new study regarding the before mentioned allegations. On the other hand, to see definitions it was necessary to raise a lot of questions about “Why me, graduated Bachelor in Painting have, chosen to post-graduate myself to start a master degree on the research theme on the teaching of visual arts? Looking for a definitive and most proper answer, started a self-narrative how I navigated in between my academical, artistics and professional ways and what exactly generated in myself (after I examined my conscience carefully) the wish into becoming a professional docent-lecturer-instructor; also have got dealt on techniques on a pedagogical intervention using freireana praxes on Proeja and what and also why, definitely has led into and caused a significant pratical time damage; and even debated how the being educated students made sense of their own works (pictures and paintings) from out of imagetic interpretation and readings on pieces of the best all time artistic master pieces (Akira Kurosawa’s Dreams-Movie), tryng by that trying by that to identify on how exact level of their very own aesthetic level they find themselves, students of the Proeja/IFPB, they had at the time of artistic production. For that reason, I brought a few authors that provided to me a proper sense of self inspirational patterns concerning imagination, cognition, aesthetical development.